Tradition and Social Identity Formation in Society - Binti Ismail, Aminah (Journal of Social Science Studies, 2021)
This article examines the role of cultural traditions and rituals in shaping individual and group social identities in a changing society. Tradition is understood as a symbolic system that functions to transmit values, strengthen social cohesion, and create identity boundaries that distinguish between groups. Through a literature study with an interpretative qualitative approach, this research examines the contribution of tradition in the process of internalizing social norms, status recognition, and the formation of meaning structures that guide social action. The results of the research show that traditions not only maintain the continuity of values, but also have the capacity to adapt to modern social dynamics, including globalization, social mobility, and the development of information technology. Traditions that are capable of undergoing symbolic reinterpretation prove more effective in maintaining their social relevance and in shaping identities that are contextual to contemporary life. Active participation in cultural rites strengthens personal and collective narratives that shape a sense of belonging and social legitimacy. This research recommends the need for an interdisciplinary approach in understanding tradition as a complex social process, as well as the importance of cultural education in nurturing the continuity of a humanized and reflective identity.